Pengembangan Sistem Manajemen Lembar Kerja Anggaran Investasi Program Rencana Kerja Rekonfigurasi Jaringan Tegangan Menengah Berbasis Web (Studi Kasus PT PLN UP3 Malang) - Maurendra Retawan Waluyo; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Medium Voltage Network Reconfiguration Work Plan Program is one of the work plan programs in the investment budget worksheet. This work plan program is used to rearrange the medium voltage network by dividing a load of electricity distribution facilities with other electricity distribution facilities. The documentation of the proposed work plan program now still uses several separated documents. It becomes ineffective task since there will be duplicated documents for the same proposal due to revisions. Changes in construction prices also cause changes in the proposed data such that manual changes need to be made for each proposal. This will take a long time process. Customer Service Unit (ULP) at this time also can't know the progress of the proposal that has been submitted. The investment budget worksheet system for the medium voltage network reconfiguration work plan program was developed to solve these problems. This system development was done in a web-based platform. Such development was done by using the Waterfall development model and an object-oriented approach. The system has been tested through several testing strategies, namely unit testing, integration testing, and validation testing. The unit and integration testings were performed by using white-box testing technique, while the validation testing were done using black-box testing technique.